Correlation between the geographical origin of Helicobacter pylori homB-positive strains and their clinical outcomes: a systematic review and meta-analysis - Masoud Keikha; Mohsen Karbalaei (BMC Gastroenterology, 2021)
Abstract Background In general, all virulence factors of Helicobacter pylori (H. pylori) are involved in its infections. However, recent studies have shown that the homB gene is one of the virulence genes that affects the severity of the clinical results of this bacterium. Methods The main purpose of this study was to investigate the relationship between the presence of homB gene in H. pylori and the progression of its infection to peptic ulcer and gastric cancer. In the present study, we conducted a systematic search to collect all articles related to the effect of homB-positive strains on clinical outcomes. Finally, 12 eligible studies according to our criteria were included in this meta-analysis and the effect of homB gene on gastric ulcer and gastric cancer diseases was evaluated by summary odds ratio (OR). Results Current results showed that the homB-positive strains significantly increase the risk of peptic ulcer (OR 1.36; 1.07–1.72 with 95% CIs), especially in western countries (OR 1.61; 1.20–2.14 with 95% CIs). Moreover, we observed a positive association between the homB gene and risk of gastric cancer (OR 2.16; 1.37–3.40 with 95% CIs). In addition, based on subgroup analysis, it was found that the presence of this gene in H. pylori strains increases the risk of gastric cancer in the Asian population (OR 3.71; 1.85–7.45 with 95% CIs). Conclusions Overall, in the present study we found that homB gene is responsible for the progressing of primary infection to severe complications, in particular peptic ulcer in western countries and gastric cancer in Asian countries.